Pemberdayaan Ibu Rumah Tangga melalui Pemanfaatan Limbah Kain Perca sebagai Produk Kreatif UMKM di Kelurahan Pendirikan Lor - Fransiska Astri Anggraeni; Dini Anggraheni (Pusat Riset dan Inovasi Nasional, 2025)
This community service program aims to empower housewives in Pendrikan Lor Subdistrict through training in processing fabric scraps into creative products, such as keychains, headbands, and brooches. This activity is expected to provide practical skills and knowledge that can be applied to establish and develop Micro, Small, and Medium Enterprises (MSMEs) based on local resources. The training is conducted in a participatory manner with a focus on hands-on practice, enabling participants to produce marketable products and enhance their economic independence. The program's outcomes demonstrate improved technical skills and motivation to start businesses, as well as positive contributions to reducing textile waste in the surrounding environment. Thus, this community service initiative supports women's economic empowerment and the development of sustainable, creative MSMEs in the region.